Pemanfaatan Fitur Gamifikasi pada Quizizz untuk Menarik Minat Belajar Siswa di Era Digital - Corry Anitaskia Agustina; Dian Ayu Pratama; Dita Aulia Al-Zamzami; Fari' Nur 'Abidah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study was motivated by the growing use of technology-based learning media. However, in reality, there are students who are inactive and easily bored during the learning process. This study employed a Systematic Literature Review (SLR) method by analyzing previous studies that were relevant to the research objective, namely the use of gamification features on Quizizz to increase students’ interest in learning in the digital age. This research is guided by three research questions: (1) Educational level that implement Quizizz; (2) The impact of Quizizz on learning motivation; (3) The most frequent subjects that uses Quizizz. The research was conducted by identifying 206 articles from 2020 to 2026, followed by screening based on titles and abstracts. Articles that did not exist in the inclusion criteria were excluded, leaving 78 articles. Subsequently, a feasibility assessment was conducted through a full reading of the articles, and in the final stage, 25 relevant articles were selected. The research results indicate that the educational level with the highest implementation rate is senior high school at 56%. The impact of Quizizz use on student learning motivation is 44%, and the most frequent subject using Quizizz is social studies with a percentage of 32%. Thus, based on the 25 identified articles, the use of Quizizz has been proven to have a positive impact on student learning motivation in the digital age.